Quantum phases of dipolar bosons in one-dimensional optical lattices - Kraus, Rebecca; Chanda, Titas; Zakrzewski, Jakub; Morigi, Giovanna (Physical Review B, 2022)
We theoretically analyze the phase diagram of a quantum gas of bosons that interact via repulsive dipolar interactions. The bosons are tightly confined by an optical lattice in a quasi-one-dimensional geometry. In the single-band approximation, their dynamics is described by an extended Bose-Hubbard model where the relevant contributions of the dipolar interactions consist of density-density repulsion and correlated tunneling terms. We evaluate the phase diagram for unit density using numerical techniques based on the density-matrix renormalization group algorithm. Our results predict that correlated tunneling can significantly modify the parameter range of the topological insulator phase. At vanishing values of the onsite interactions, moreover, correlated tunneling promotes the onset of a phase with a large number of low-energy metastable configurations.
Created from Fastlane, Scopus look-up